Semi-analytical solutions of ordinary differential equations - Goździewski, Krzysztof; Maciejewski, Andrzej J. (Zielona Góra: Uniwersytet Zielonogórski)
We describe the method that allows, in many cases, to solve effectively a wide class of ordinary differential equations describing a mechanical system. The method is based upon the idea of normalization procedure. We present its implementation and some examples of its applications.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka